2016
DOI: 10.14214/sf.1628
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and nitrogen balance of naturally afforested silver birch (<i>Betula pendula</i> Roth.) stand in Estonia

Abstract: Highlights• Leafless aboveground biomass of the 17-year-old natural silver birch stand growing in abandoned agricultural land reached 94 Mg ha -1 .• The largest fluxes in N budget were net nitrogen mineralization and gaseous N 2 -N emission.• Nitrogen leaching was low.• Soil N content increased with the stand age, soil C content remained stable.• N 2 O and N 2 fluxes in boreal deciduous forest were analysed. AbstractSilver birch (Betula pendula Roth.) is one of the main pioneer tree species occupying large are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Since the energy from renewable resources has been widely promoted, the production of large quantities of easily accessible and useable highly energetic biomass from trees has gained attention, leading to the publication of numerous research papers on the ecological processes for modelling such ecosystems (e.g., [9][10][11][12][13][14][15][16][17][18][19][20]). Many of the published papers also consider the environmental aspects, including carbon sequestration and allocation of elements (e.g., [21][22][23][24][25][26]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the energy from renewable resources has been widely promoted, the production of large quantities of easily accessible and useable highly energetic biomass from trees has gained attention, leading to the publication of numerous research papers on the ecological processes for modelling such ecosystems (e.g., [9][10][11][12][13][14][15][16][17][18][19][20]). Many of the published papers also consider the environmental aspects, including carbon sequestration and allocation of elements (e.g., [21][22][23][24][25][26]).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies of birch plantations in Baltic countries (Liepiņš, 2011) and in naturally regenerated birch stands (Aosaar et al, 2016) covering an age range from 15 to 20 years, report birch MAI (Mean Annual Increment) around 10 m 3 ha-1 yr-1 (Lutter, 2017). However, the mean annual increment of beech and birch in 1 ha is 2.3 and 3 m 3 , respectively, in the existing forests in Turkey (State Planning Organization, 2001).…”
Section: Economic Analysis 32 Ekonomska Analizamentioning
confidence: 99%
“…Author is lecturer at Artvin Çoruh University, Artvin Vocational School, Materials and Material Processing, Artvin, Turkey 2. Authors are research assistant and professor at the Karadeniz Technical University, Faculty of Forestry, Department of Forest Industry Engineering, Trabzon, Turkey 1. Autor je predavač Sveučilišta Artvin Çoruh, Strukovna škola Artvin, Materijali i obrada materijala, Artvin, Turska 2.…”
mentioning
confidence: 99%
“…Birch trees intensively uptake N (56 kg ha − 1 yr − 1 ), P (4.1 kg ha − 1 yr − 1 ), K (28 kg ha − 1 yr − 1 ), and calcium (Ca, 44 kg ha − 1 yr − 1 ) (Ovington and Madgwick 1959), with the process reaching a maximum intensity in the early stages of growth (Miller 1984). Daugaviete et al (2003) and Aosaar et al (2016) reported positive effects of birch trees on soil N during the rst few years after afforestation. Additionally, Uri et al (2012) and Gawęda et al (2014) observed increasing contents of the major nutrients in soils under birch chronosequences.…”
Section: Introductionmentioning
confidence: 99%